NOVEL 2X2 FULL-RATE SPACE-TIME BLOCK CODE WITH IMPROVED PERFORMANCE AT SMALL SEPARATION BETWEEN COLLOCATED ANTENNAS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
In this paper, we introduce a novel full rate 2X2 space-time block code and compare its FER and BER performance against that of the Golden code by way of computer simulations using a mathematical model that takes the distance between collocated antennas as a parameter. For d = 1 λ, where λ is the wavelength of the carrier frequency, the superiority of the new code is obvious. For d = 2 λ, the Golden code is better, but the new space-time block code still works rather well. While we do not provide here plots for d = λ/2, we know from our experiments that our new code shows only a gracious degradation as compared to the case d = 1 λ. This recommends the new code for applications where a small distance between collocated antennas is unavoidable. The main originality of the new code is using two signal constellations instead of a single one, as detailed in the body of our work. In so doing, we also greatly simplified the issue of determining the separators and the shapers, which are rather complex in the case of the Golden code.
Keywords: Alamouti code; Golden code; Linear dispersion codes; Space-time block coding; Transmitter antenna diversity